Academic cooperation strategies for the development of training and research in Central America and the European Union - Trejos-Benavides, Eugenio (2013)
The article summarizes the actions for the institutional strengthening and research projects for the training and research of the agribusiness capacities in Costa Rica and the Region of Murcia. The training of teachers, graduates and students; the knowledge of agribusiness and rural tourism companies, social economy and the development of agribusiness, the creation of spin-off, logistics and the operations of horticultural companies are some of the main objectives of academic cooperation projects for the development of the Central American countries and the European Union. These aspects of the research will lead to a better understanding of rural areas and agricultural activities to encourage the consolidation in the regions.